Analisis Budaya Organisasi: Perspektif Teori Hofstede Pada Himpunan Mahasiswa Ilmu Administrasi Negara (HIMANISRA) - Aryo Bagus Ramadhan; Siti Nur Azizah; Asna Choirul Ibad; Refanda Farah Yasmin; Verina Rahma Widiasari; Joko Tri Nugraha (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study examines the organizational culture of HIMANISRA, the Public Administration student association at Universitas Tidar, using a quantitative descriptive method to provide an empirical overview of members’ perceptions. All 57 active members participated through census sampling, ensuring that the findings represent the entire organizational population. The measurement instrument adapted from Hofstede et al. (1993) demonstrated reliable consistency, confirmed by a Cronbach’s Alpha value of 0.762, indicating that the items were appropriate for assessing cultural dimensions within the association The results show that HIMANISRA possesses a generally strong organizational culture reflected in members’ commitment, cooperation, willingness to communicate openly, and clarity in understanding roles and responsibilities. Collective decision-making is widely practiced, and interpersonal relations are characterized by trust, friendliness, and supportive interactions. Members also show initiative and active participation in organizational activities, contributing to a conducive environment for collaboration. Additionally, inter-division cooperation appears to function effectively, supporting organizational stability and operational smoothness. However, some aspects still require attention. The uniformity of rules across divisions is not fully consistent, and leadership attention is perceived as uneven among members. Furthermore, not all members feel involved in innovation processes, suggesting the need to strengthen inclusive participation. These findings highlight that although core cultural values are well internalized, their practical implementation needs improvement. Strengthening communication mechanisms, ensuring equitable leadership engagement, and expanding participatory practices are essential steps for developing a more adaptive and sustainable organizational culture within HIMANISRA